Historical approach of contemporary understanding of school in globalization - Parlić Božović, Jasna Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
Intercultural education repects and promotes diversity in all areas of human life. This phenomenon indicates that people naturally and spontaneously develop different lifestyles, different customs and worldviews. These differences need to be considered as a wealth of life. When we talk about education, and school as a narrow concept, in which the differences are usually promoted, have a vision of a community that provides equal opportunities, opposes injustice and discrimination, and strives for the values on which is being built equality. Especially, this phenomenon is being pointed up in our conditions, when we are still adapting reforms of globalization. In the Contemporary World, promoting the democracy becomes a key goal of education, as well as in a whole society. Therefore, in the education system often takes into account the multicultural character of the society that tends to active contribution to a peaceful coexistence and positive interaction between different cultural groups. Traditionally, in this sense, identifies two approaches in education: multicultural education that through learning about other cultures strive to provide the acceptance and tolerance of other cultures. On the other side, we have the intercultural education that aims to overcome the passive coexistence and achieve developed and sustainable way of living together in a multicultural society. This is achieved through the construction process of understanding, mutual respect and dialogue among groups of different cultures, then, ensuring equal opportunities and combating discrimination.